Strategi Pengembangan Usaha Pindang pada CV Putra Kresna Desa Brondong Kabupaten Lamongan - Rusdiana, Nur Devi Arum; Tain, Anas; Sutanto, Adi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The establishment of a business will require an appropriate strategy in developing the business. The smoked fish business CV Putra Kresna in Brondong Village, Lamongan Regency, is one of the well-known businesses in processing smoked fish in Lamongan. This research aims to: (1) analyze the internal and external environmental conditions of the smoked fish business CV. Putra Kresna, (2) analyze the strengths, weaknesses, opportunities and threats of the smoked fish business at CV Putra Kresna, (3) analyze the business development strategy of the smoked fish business at CV. Putra Kresna. This research is used to obtain descriptive qualitative data. The methods used are observation, interviews, questionnaires and documentation. The research focus is aimed at the internal and external environmental conditions as well as the appropriate marketing development strategy to be applied to the smoked fish business of Cv Putra Kresna. The research location was carried out at the location of Cv Putra Kresna in Brondong Village, Lamongan Regency. Data analysis was carried out using SWOT matrix analysis, and IE Matrix. After analyzing the results of the internal and external conditions of the smoked fish business marketing of Cv Putra Kresna, the main strength lies in the ease of obtaining raw materials, the main weakness lies in the limited distribution channels to modern markets, the main opportunity lies in the business development of smoked fish and the main threat lies in government regulations related to food product standardization. The formulation of alternative strategies using the SWOT matrix resulted in four alternative marketing developments for the Smoked Fish Business Cv Putra Kresna, namely (1) Utilizing proximity to fish landing sites to obtain fresh raw materials in a short time after fishermen's catches; (2) Developing distribution channels; (3) Increasing product innovation; (4) Ensuring compliance with government regulations regarding food product standardization.